The Influence Of School Environment On Academic Performance Of Secondary School Students In Kuala Terengganu, Malaysia - Norsuhaily, Abu Bakar (2015)
The aim of this study is to examine how school environment influence students’ academic performance. The main objective of the study is to analyse how school facilities, teachers and environment significantly affect secondary school students’ academic performance in Kuala Terengganu, Malaysia. Descriptive Survey Research design was used in which data from 377 respondents was collected using self-administered questionnaire from 4 selected secondary schools within Kuala Terengganu. Stratified random sampling technique was used to sample the respondents. The data was analysed using regression analysis. The result is explained in three forms; Demographic information, descriptive analysis and inferential analysis. The result of the study indicated that students from a school with adequate facilities, good teachers and favourable environment perform well than those from schools with fewer facilities, unqualified teachers and the less enabling environment. Finally, recommendations were given to parents, teachers, policy makers and educational administrators